Surface nitrous oxide concentrations and fluxes from water bodies of the agricultural watershed in Eastern China. (August 2019) - Xiao, Qitao; Hu, Zhenghua; Fu, Congsheng; Bian, Hang; Lee, Xuhui; Chen, Shutao; Shang, Dongyao
Abstract: Agriculture is one of major emission sources of nitrous oxide (N2 O), an important greenhouse gas dominating stratospheric ozone destruction. However, indirect N2 O emissions from agriculture watershed water surfaces are poorly understood. Here, surface-dissolved N2 O concentration in water bodies of the agricultural watershed in Eastern China, one of the most intensive agricultural regions, was measured over a two-year period. Results showed that the dissolved N2 O concentrations varied in samples taken from different water types, and the annual mean N2 O concentrations for rivers, ponds, reservoir, and ditches were 30 ± 18, 19 ± 7, 16 ± 5 and 58 ± 69 nmol L −1, respectively. The N2 O concentrations can be best predicted by the N O 3 − -N concentrations in rivers and by the N H 4 + -N concentrations in ponds. Heavy precipitation induced hot moments of riverine N2 O emissions were observed during farming season. Upstream waters are hot spots, in which the N2 O production rates were two times greater than in non-hotspot locations. The modeled watershed indirect N2 O emission rates were comparable to direct emission from fertilized soil. A rough estimate suggests that indirect N2 O emissions yield approximately 4% of the total N2 O emissions yield from N-fertilizer at the watershed scale. Separate emission factors (EF) established for rivers, ponds, and reservoir were 0.0013, 0.0020, and 0.0012, respectively, indicating that the IPCC (Inter-governmental Panel on Climate Change) default value of 0.0025 may overestimate the indirect N2 O emission from surface water in eastern China. EF was inversely correlated with N loading, highlighting the potential constraints in the IPCC methodology for water with a high anthropogenic N input. Graphical abstract: Image 1 Highlights: N2 O concentrations and fluxes from water bodies of the agricultural watershed in eastern China varied seasonally and spatially. N loadings and precipitation best predicted the N2 O emission hot spots and hot moments and hot spots. Separate emission factors for different seasonas and water types may be required to accurately estimate the indirect N2 O emission. Abstract : The surface indirect N2 O emission rates were comparable to direct emission, but the IPCC default emission factor may overestimate indirect N2 O emission in the region.